2020
DOI: 10.1177/0009922820913960
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Symptoms Predict School Attendance After Pediatric Concussion

Abstract: This study examined the relationship between postconcussive symptom domain and school attendance. Retrospective chart review was completed for 88 children aged 6 to 18 years who were evaluated within 30 days postinjury. Hierarchical multiple regression was used to assess the association of physical, cognitive, emotional, and sleep symptoms with extent of school attendance. A subgroup multiple regression analysis was conducted to evaluate whether age affected the relationship of symptoms to school attendance. A… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(16 citation statements)
references
References 30 publications
0
16
0
Order By: Relevance
“…In a study of 88 children and adolescents, subjective sleep symptoms were shown to be a significant predictor of postconcussion school attendance. 17 Other studies have found that children and adolescents deemed to have poor sleep quality using the Pittsburgh Sleep Quality Index took significantly longer to reach symptom resolution and to be cleared to return to play following concussion. 11 Another study found that adolescents with subjective sleep symptoms had a 3-to 4-fold increase in symptom resolution time when compared with adolescents without self-reported sleep symptoms.…”
Section: Discussionmentioning
confidence: 97%
“…In a study of 88 children and adolescents, subjective sleep symptoms were shown to be a significant predictor of postconcussion school attendance. 17 Other studies have found that children and adolescents deemed to have poor sleep quality using the Pittsburgh Sleep Quality Index took significantly longer to reach symptom resolution and to be cleared to return to play following concussion. 11 Another study found that adolescents with subjective sleep symptoms had a 3-to 4-fold increase in symptom resolution time when compared with adolescents without self-reported sleep symptoms.…”
Section: Discussionmentioning
confidence: 97%
“…School attendance, evaluated as missed days of school after concussion, was reported in 20 studies. Of these, 2 focused on college students, 42,43 6 were adolescents, 16,19,[44][45][46][47] and 12 were mixedage groups. 3,[48][49][50][50][51][52][53][54][55][56][57] Absences from school ranged widely, from a mean of 3 to 69.2 days.…”
Section: Question 1: What Are Academic Outcomes Following Concussion?mentioning
confidence: 99%
“…Academic accommodations, communication between medical providers and schools, and receiving academic accommodations and medical care, including therapy-based interventions, were positive factors for post-concussion academic experiences. 45,53,54,[66][67][68]70,73,74 However, estimates were not provided to measure the association between each post-injury factor and academic outcomes.…”
Section: Question 3: What Factors Are Associated With Student Outcome...mentioning
confidence: 99%
“…8,87 Healthcare entry points were frequent barriers. 8,14,73,84,89,117,126 Fewer than half of patients seen by a primary care physician were provided academic accommodations, 14,87 and 95% of patients seen in the emergency department were not provided accommodations. 78 physician, 105,117,127 many students appear to be at risk for not receiving accommodations.…”
Section: Empiricalmentioning
confidence: 99%